Effects of Ramipril on the Aldosterone/Renin Ratio and the Aldosterone/Angiotensin II Ratio in Patients With Primary Aldosteronism - Guo, Zeng; Poglitsch, Marko; Cowley, Diane; Domenig, Oliver; McWhinney, Brett C.; Ungerer, Jacobus P.J.; Wolley, Martin; Stowasser, Michael (Hypertension (Dallas, Tex. 1979), 2020)
The aldosterone/renin ratio (ARR) is currently considered the most reliable approach for case detection of primary aldosteronism (PA). ACE (Angiotensin-converting enzyme) inhibitors are known to raise renin and lower aldosterone levels, thereby causing false-negative ARR results. Because ACE inhibitors lower angiotensin II levels, we hypothesized that the aldosterone/equilibrium angiotensin II (eqAngII) ratio (AA2R) would remain elevated in PA. Receiver operating characteristic curve analysis involving 60 patients with PA and 40 patients without PA revealed that the AA2R was not inferior to the ARR in screening for PA. When using liquid chromatography-tandem mass spectrometry to measure plasma aldosterone concentration, the predicted optimal AA2R cutoff for PA screening was 8.3 (pmol/L)/(pmol/L). We then compared the diagnostic performance of the AA2R with the ARR among 25 patients with PA administered ramipril (5 mg/day) for 2 weeks. Compared with basally, plasma levels of equilibrium angiotensin I (eqAngI) and direct renin concentration increased significantly (P<0.01 or P<0.05) after ramipril treatment, whereas eqAngII and ACE activity (eqAngII/eqAngI) decreased significantly (P<0.01). The changes of plasma renin activity and plasma aldosterone concentration in the current study were not significant. On day 14, 4 patients displayed false-negative results using ARR_direct renin concentration (plasma aldosterone concentration/direct renin concentration), 3 of whom also showed false-negative ARR_plasma renin activity (plasma aldosterone concentration/plasma renin activity). On day 15, 2 patients still demonstrated false-negative ARR_plasma renin activity, one of whom also showed a false-negative ARR_direct renin concentration. No false-negative AA2R results were observed on either day 14 or 15. In conclusion, compared with ARR which can be affected by ACE inhibitors causing false-negative screening results, the AA2R seems to be superior in detecting PA among subjects receiving ACE inhibitors.